2023
DOI: 10.3389/fpsyt.2023.1137071
|View full text |Cite
|
Sign up to set email alerts
|

Prospective acceptability of digital phenotyping among pregnant and parenting people with opioid use disorder: A multisite qualitative study

Abstract: BackgroundWhile medications for opioid use disorder (MOUD) effectively treat OUD during pregnancy and the postpartum period, poor treatment retention is common. Digital phenotyping, or passive sensing data captured from personal mobile devices, namely smartphones, provides an opportunity to understand behaviors, psychological states, and social influences contributing to perinatal MOUD non-retention. Given this novel area of investigation, we conducted a qualitative study to determine the acceptability of digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Our findings that participants were mostly unconcerned with the use of tracking elements in research and intervention are supported by high rates of feasibility and acceptability of both ecological momentary assessment 9,24 -26 and GPS tracking 16,27 in similar populations of people who use substances. Participant concerns around confidentiality 28 and the time and effort burden of data collection have been documented elsewhere among people who use drugs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our findings that participants were mostly unconcerned with the use of tracking elements in research and intervention are supported by high rates of feasibility and acceptability of both ecological momentary assessment 9,24 -26 and GPS tracking 16,27 in similar populations of people who use substances. Participant concerns around confidentiality 28 and the time and effort burden of data collection have been documented elsewhere among people who use drugs.…”
Section: Discussionsupporting
confidence: 52%
“…Participant concerns around confidentiality 28 and the time and effort burden of data collection have been documented elsewhere among people who use drugs. 16,29,30 Similarly, perceived participant benefits related to study participation, including increased self-worth and social support along with decreased substance use, have also been observed elsewhere. 31 To our knowledge, this is the first study discussing specific perceived benefits to participation in studies using ecological momentary assessment and GPS tracking among people who use substances.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The TFA defines acceptability as a multifaceted construct, comprising of seven domains (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy, see Table 1 for construct definitions) that can be applied at different timepoints (before, during or after an intervention) to assess the prospective, concurrent, or retrospective acceptability of an intervention. Perinatal research has used the TFA to assess acceptability in a variety of healthcare contexts (e.g., 57 61 ), including the use of exposure therapy among pregnant women with elevated anxiety ( 62 ), and a systematic review on the acceptability of implementing patient reported measures in routine maternity care ( 63 ). However, the authors know of no research that has used the TFA to assess the acceptability of suicide-related screening items to perinatal women.…”
Section: Introductionmentioning
confidence: 99%